Structural construction of law enforcement acts - Пунько, Оксана Віталіївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The article investigates the problematic issue of structural construction of law enforcement acts, its components, internal and external form of construction. The task of this article is outlining the theoretical position of structural construction of law enforcement acts. Law enforcement act is the legal result of law enforcement activities. These acts are fixed, issued decisions that were taken in law enforcement activity. Analysis of law enforcement practices shows that most acts are issued in the form of a written document and have a clear structure.